Impact of child's cognitive and social-emotional difficulties on child abuse: Does mother's justification of intimate partner violence also play a role?. (July 2021) - Afiaz, Awan; Masud, Mohammad Shahed; Mansur, Mohaimen
Highlights: Nearly two-thirds of all children in Bangladesh experience physical abuse in households. Physical abuses are perpetrated mostly against younger children. Children with cognitive and social-emotional difficulties face higher risk of abuse. Mothers who justify IPV are more likely to physically abuse their children. Media interventions and programs may prove to be useful for LMICs. Abstract: Background: Violence against children has been a persistent problem in developing nations. The adverse effects of physical violence bear a considerable impact on children's physical and psychological development resulting in both short and long-term issues. Objective: The aim of this study was to explore whether children with cognitive and social-emotional difficulties (CSEDs) were at a higher risk of experiencing physical abuse and whether mothers' views on intimate partner violence (IPV) were also related to physical abuse against children. Participants and Setting: The Bangladesh Multiple Indicator Cluster Survey-2019 was used with a sample of 27, 086 children aged 5–14. Methods: Generalized linear modelling along with a machine learning method of classification trees was employed to investigate the important sociodemographic characteristics and identify the most vulnerable groups of children based on their likelihood of exposure to household-violence. Results: Nearly 62.5 % of the children were physically abused by their mothers. Children with CSEDs were 53 % (OR 1.53; 95 % CI: 1.41, 1.67) more likely to experience physical abuse and mothers' justification of IPV was associated with a 16 % higher risk (OR 1.16; 95 % CI: 1.08, 1.26). Moreover, younger children aged 11 or below belonged to the high-risk groups of experiencing abuse. Conclusions: The findings suggest that violence against children is widespread in Bangladesh, especially in children having CSEDs. Mothers' acceptance of IPV was also associated with increased abusive practice against children. Sincere focus on these issues is imperative if Bangladesh intends to achieve the sustainable development goal 16.2 of eradicating all forms of violence against children and ensure their safe development.